EFFECT OF DEFERENT GESTATION PERIOD ON SERUM ESTROGEN, PROGESTERONE AND SOME BIOCHEMICAL PARAMETERS IN AWASSI EWES - Maythem A. Ismaeel,; Omar. Sh. Saed,; Nawaf. N. Dhahir, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was designed to investigate the influence of different gestation periods on serum estrogen, progesterone and biochemical attributes levels in Awassi ewes. Ten ewes of 2-5 years old and 35-50 kg live body weight were used currently during the period from September 2019 to February 2020. Estrogen concentration seemed to decline since 2nd month and reached its lesser level at 4th month and re-increased at 5th month of gestation. The progesterone level increased (P≤0.05) at 2nd and 3rd months and decreased at 5th month of gestation. Serum  Cholesterol, glucose, total protein, albumin and glubulin were decreased (P≤0.05) at the last gestation period. AST, ALT, and ALP activities take similar trend being decreased at the last gestation period. In conclusion estrogen, progesterone and other blood biochemical parameters were changed obviously during different gestation periods of Awassi ewes.